Silver nanoparticles in soil-plant systems - Anjum, Naser A. (2018)
Silver nanoparticles (AgNPs) have broad spectrum antimicrobial/biocidal properties against all classes of microorganisms and possess numerous distinctive physico-chemical properties compared to bulk Ag. Hence, AgNPs are among the most widely used engineered NPs in a wide range of consumer products and are expected to enter natural ecosystems including soil via diverse pathways. However, despite: (i) soil has been considered as a critical pathway for NPs environmental fate, (ii) plants (essential base component of all ecosystems) have been strongly recommended to be included for the development of a comprehensive toxicity profile for rapidly mounting NPs in varied environmental compartments, and (iii) the occurrence of an intricate relationship between "soil-plant systems" where any change in soil chemical/biological properties is bound to have impact on plant system, the knowledge about AgNPs in soils and investigations on AgNPs-plants interaction is still rare and in its rudimentary stage. To this end, the current paper: (a) overviews sources, status, fate, and chemistry of AgNPs in soils, AgNPs-impact on soil biota, (b) critically discusses terrestrial plant responses to AgNPs exposure, and (c) illustrates the knowledge-gaps in the current perspective. Based on the available literature critically appraised herein, a multidisciplinary integrated approach is strongly recommended for future research in the current direction aimed at unveiling the rapidly mounting AgNPs-fate, transformation, accumulation, and toxicity potential in "soil-plant systems," and their cumulative impact on environmental and human health.